Infections and the development of childhood acute lymphoblastic leukemia: a population-based study. Issue 6 (November 2020) - Hwee, Jeremiah; Sutradhar, Rinku; Kwong, Jeffrey C.; Sung, Lillian; Cheng, Stephanie; Pole, Jason D.
Abstract : An infectious trigger for childhood acute lymphoblastic leukemia is hypothesized and we assessed the association between the rate, type, and critical exposure period for infections and the development of acute lymphoblastic leukemia. We conducted a matched case-control study using administrative databases to evaluate the association between the rate of infections and childhood acute lymphoblastic leukemia diagnosed between the ages of 2–14 years from Ontario, Canada and we used a validated approach to measure infections. In 1600 cases of acute lymphoblastic leukemia, and 16 000 matched cancer-free controls aged 2–14 years, having >2 infections/year increased the odds of childhood acute lymphoblastic leukemia by 43% (odds ratio = 1.43, 95% confidence interval 1.13–1.81) compared to children with ⩽0.25 infections/year. Having >2 respiratory infections/year increased odds of acute lymphoblastic leukemia by 28% (odds ratio =1.28, 95% confidence interval 1.05–1.57) compared to children with ⩽0.25 respiratory infections/year. Having an invasive infection increased the odds of acute lymphoblastic leukemia by 72% (odds ratio =1.72, 95% confidence interval 1.31–2.26). Having an infection between the age of 1–1.5 years increased the odds of acute lymphoblastic leukemia by 20% (odds ratio = 1.20, 95% confidence interval 1.04–1.39). Having more infections increased the odds of developing childhood acute lymphoblastic leukemia and having an infection between the ages of 1–1.5 years increased the odds of childhood acute lymphoblastic leukemia. Abstract : Supplemental Digital Content is available in the text.